The effectiveness of paaryaad and braitonic training on executive functions of children with learning disabilities - Ramazani Baghmisheh L; Salehian MH; Hosseinzadeh Peyghan R (Penerbit UKM, 2023)
The purpose of this research was to compare the effectiveness of braitonic and paaryaad trainings on executive functions on children with learning disabilities. This research applied semi-experimental method. The research was performed in two stages which are pre-test and post-test. The statistical population was children with learning disabilities (45 participants) referred to Tabriz Welfare Center who were voluntary. N-back test was used to measure working memory while Psychomotor task software and Go/ No Go test were used to measure inhibition. After dividing the children into three groups, the braitonic and paaryaad training programs for the two experimental groups were designed and measured according to the children’s condition and the components of executive function (working memory and inhibition) in two stages. Analysis of variance test was used to compare the variables in children’s executive function. The findings demonstrated braitonic trainings and paaryaad trainings improved the level of executive functions of children with learning disabilities. The effect of paaryaad trainings was significantly greater than the effect of braitonic trainings in increasing the level of executive functions of children with learning disabilities.